Simultaneous measurements of indoor radon and thoron and inhalation dose assessment in Douala City, Cameroon. Issue 5 (3rd September 2019) - Serge Didier, Takoukam Soh; Saïdou,; Tokonami, Shinji; Hosoda, Masahiro; Suzuki, Takahito; Kudo, Hiromi; Bouba, Oumarou
ABSTRACT: Radon, thoron and associated progeny measurements have been carried out in 71 dwellings of Douala city, Cameroon. The radon–thoron discriminative detectors (RADUET) were used to estimate the radon and thoron concentration, while thoron progeny monitors measured equilibrium equivalent thoron concentration (EETC). Radon, thoron and thoron progeny concentrations vary from 31 ± 1 to 436 ± 12 Bq m –3, 4 ± 7 to 246 ± 5 Bq m –3, and 1.5 ± 0.9 to 13.1 ± 9.4 Bq m –3 . The mean value of the equilibrium factor for thoron is estimated at 0.11 ± 0.16. The annual effective dose due to exposure to indoor radon and progeny ranges from 0.6 to 9 mSv a –1 with an average value of 2.6 ± 0.1 mSv a –1 . The effective dose due to the exposure to thoron and progeny vary from 0.3 to 2.9 mSv a –1 with an average value of 1.0 ± 0.4 mSv a –1 . The contribution of thoron and its progeny to the total inhalation dose ranges from 7 to 60 % with an average value of 26 %; thus their contributions should not be neglected in the inhalation dose assessment.